EFFECT OF FOLIAR APPLICATION OF AMINO ACIDS, BENZYL ADENINE, AND NANO NPK ON POLLEN TRAITS, AND SOME CHARACTERISTICS OF GRAPE - Derin Ali Rashid; Shawkat M. Al-Atrushy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was carried out in a private vineyard, located in Sulaymaniyah governorate, Kurdistan region-Iraq, during the growing season (2022) to investigate the effect of foliar applications of amino acids (0, 5, 10 mL.L-1), benzyl adenine (0, 100, 200 mg.L-1), and Nano-NPK fertilizer (0, 2, 4 g.L-1) and their interactions on the activity of pollen grains and some chemical components. The results confirmed that 10 mg.L-1 amino acid produced the highest pollen viability, pollen germination, leaf chlorophyll content, total carotene, and vitamin C, while it caused a significant decrease in total phenol compared to the control. Benzyl adenine, 200mg.L-1 gave the highest significant values of the undertaken parameters except for phenol and vitamin C, they were not affected by spraying BA. Nano-NPK fertilizer at 4g.L-1 poduced the highest significant means of parameters. Meanwhile, the triple interaction effects of 10 mg.L-1 AA + 200mg.L-1 BA + 4g.L-1 Nano-NPK obtained the superior significant values of pollen viability, pollen germination, leaf chlorophyll content, total carotene, vitamin C, the least significant value of total phenol compared to the remainder treatment combinations and control.